ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA ALAFAMART CABANG PARIS 2 KOTA PONTIANAK - Rizky, Muhammad B1031151076 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
Internal control in a developing company is now very necessary in carrying out company operations. The goods purchased are the most valuable assets in a trading company, because they are the most inactive items in a trading company. One managerial that is very important in the company's operations that control internally.In this study, researchers used a case study on Alfamart Paris Branch 2 Pontianak City. With the aim to study and analyze the internal control of procurement of goods implemented by Alfamart Paris 2 Branch Pontianak. In data analysis, the technique used is qualitative analysis, namely the internal analysis method for merchandise inventory,Based on the results of this study it can be concluded that the internal control system for the merchandise inventory in this company uses an internal control method called the Organizational Structure, Flowchart, Internal Control Questionnaire (ICQ) when it is available is quite effective. Aini, N., Fatmaningrum, W., Yusuf, A. (2011). Upaya Meningkatkan Perilaku Pasien Dalam Tatalaksana Diabetes Melitus Dengan Pendekatan Teori Model Behavioral System Dorothy E. Johnson. Jurnal Ners Vol. 6 No. 1 April 2011. Surabaya: FK Unair Surabaya.Arianti, D.F. (2003). Evaluasi Sistem Akuntansi Pengeluaran Barang Pada PT. Amalia. Skripsi.Halim, Abdul.  (2007). Akuntansi Keuangan Daerah. Jakarta: Salemba Empat.Hall, James A. (2011). Sistem Informasi Akuntansi. Edisi Keempat. Jakarta: Salemba Empat.Handayani, Siti. (2014). Evaluasi Pengendalian Internal Sediaan Barang Pada Toko Kesongo Tuntang. Semarang: Perpustakaan Universitas Dian Nuswantoro. Skripsi Tidak Dipublikasikan.Hery. (2009). Akuntansi Keuangan Menengah. Jakarta: Bumi Aksara.Jogiyanto, H.M. (2005). Analisa dan Desain Sistem Informasi: Pendekatan Terstruktur Teori dan Praktik Aplikasi Bisnis. Yogyakarta: Andi.Kotler, Philip. (2006). Manajemen Pemasaran Jilid I. Edisi Kesebelas. Jakarta: PT. Indeks Gramedia.Krismiaji. (2002). Sistem Informasi Akuntansi. Yogyakarta: UPP AMP YKPN.Krismiaji. (2010). Sistem Informasi Akuntansi. Yogyakarta: UPP AMP YKPN.Mulyadi. (2001). Sistem Akuntansi. Edisi Ketiga. Jakarta: Salemba Empat.Mulyadi. (2009). Akuntansi Biaya. Edisi Kelima. Yogyakarta: STIE YPKPN.Ompusunggu, Halomoan. (2002). Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Efektivitas Pelaksanaan Sistem Pengendalian Intern. Jurnal Akuntansi Universitas Jendral Sudirman. Skripsi.Pedoman Penulisan Karya Akhir. (2017). Pontianak: Fakultas Ekonomi dan Bisnis Universitas Tanjungpura.Romney,  Marshal  B  &  Paul  John  Steintbart. (2006). Accounting Information System. Edisi Kesembilan. Jakarta: Salemba Empat.Setiawan, Chandra. (2017). Analisis Sistem Pengendalian Internal Persediaan Pada PD Andhika Primajaya (Distributor Unilever Pontianak). Skripsi.Sugiyono. (2014). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Susanto, A. (2013). Sistem Informasi Akuntansi. Bandung: Lingga Jaya.Suwardjono. (2003). Akuntansi Pengantar. Yogyakarta: BPFE.Syam, Saddam. (2015). Human Error Dalam Proses Picking Dan Shipping Warehouse Management Di PT Cipta Krida Bahari Samarinda. Skripsi.Tamodia, Widya. (2013). Evaluasi Penerapan Sistem Pengendalian Intern Untuk Persediaan Barang Dagangan Pada PT. Laris Manis Utama Cabang Manado. Manado: Universitas Sam Ratulangi Manado. Skripsi.Tuanakotta, T. M. (2015). Audit Kontemporer. Jakarta: Salemba Empat.Warren et al. (2005). Prinsip-Prinsip Akuntansi. Jakarta: Salemba Empat.www.coso.org